2022
DOI: 10.1177/17454999221143847
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel analysis of teacher professional well-being and its influential factors based on TALIS data

Abstract: The current study examines how teachers’ professional wellbeing is affected by teacher-level and school-level factors using the TALIS 2018 data. Teacher-level factors consist of teachers’ instructional practices and teachers’ professional practices and school-level factors include school climate, school leadership styles and workload. The Hierarchical Linear Modeling (HLM) was used to examine whether the principals’ leadership, school climate and workload and teachers’ instructional practices and teachers’ pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…Similarly, Holzberger et al [58] conducted a longitudinal follow-up survey, illustrating that instructional practices significantly predicted teachers' self-efficacy. Moreover, analyses using TALIS 2018 data confirmed the positive influence of instructional practices on teachers' self-efficacy, a trend observed across diverse cultural contexts, including Chinese, Canadian, Finnish, Japanese, and Singaporean settings [59]. In light of the literature analysis, this study posits Hypothesis 4: Hypothesis 4a.…”
Section: Student-centered Teaching Practices and Teacher Self-efficacysupporting
confidence: 55%
“…Similarly, Holzberger et al [58] conducted a longitudinal follow-up survey, illustrating that instructional practices significantly predicted teachers' self-efficacy. Moreover, analyses using TALIS 2018 data confirmed the positive influence of instructional practices on teachers' self-efficacy, a trend observed across diverse cultural contexts, including Chinese, Canadian, Finnish, Japanese, and Singaporean settings [59]. In light of the literature analysis, this study posits Hypothesis 4: Hypothesis 4a.…”
Section: Student-centered Teaching Practices and Teacher Self-efficacysupporting
confidence: 55%
“…Similarly, Holzberger et al [54] conducted a longitudinal follow-up survey, illustrating that instructional practices significantly predicted teachers' self-efficacy. Moreover, analyses using TALIS 2018 data confirmed the positive influence of instructional practices on teachers' self-efficacy, a trend observed across diverse cultural contexts, including Chinese, Canadian, Finnish, Japanese, and Singaporean settings [55].…”
Section: Student-centered Teaching Practices and Teacher Self-efficacymentioning
confidence: 72%
“…Some researchers claim that components of the quality of working life can vary depending on a profession (Bearfield, 2003). The study on the quality of working life and differences between the causes of dissatisfaction of representatives from different professional groups revealed that different groups had their own specific problems (Adriaenssens, De Gucht, & Maes, 2015;Kouhsari, Chen, & Baniasad, 2023;Dreer, 2021;Kang et al, 2020;Kouhsari, Chen & Baniasad, 2023;Kovalenko, Hryschuk, & Rohal, 2020;Voitenko, Myronets, Osodlo, Pozdnyshev, & Hordynia, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most proposed theoretical models have many limitations, primarily related to the narrow definitions of professional well-being due to differences in approaches to the study of this phenomenon (for example, subjective well-being in professional activity (Dreer, 2021;Dugan, Ubal & Scot, 2023;Pankovets, 2004;Pidbutska, 2014); job satisfaction ( Kouhsari, Chen & Baniasad, 2023;Spector, 1997); quality of working life (Manira et al, 2018;Sirgy, 2001;Ellis, 2002), professional well-being (Pakhol, 2018;Voitenko, Myronets, Osodlo, Pozdnyshev, & Hordynia, 2022;Van Horn, 2004;Warr, 2013;Schultz, 2009 and others) and insufficient psychometric reliability of the obtained data (nonreproducibility of most of authors' factor models).…”
Section: Introductionmentioning
confidence: 99%